Duration of Work and Body Position on Carpal Tunnel Syndrome among BNI Employees in Denpasar City - Sancitawati, Ida Ayu Diah; Saraswati, Ni Luh Putu Gita Karunia; Juhanna, Indira Vidiari; Pramita, Indah (Bachelor and Profession of Physiotherapy Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2024)
Introduction: Typing activities at work involving repetitive movements with static body posture, if not adequately addressed, can lead to Carpal Tunnel Syndrome (CTS). Data from the National Health Interview Study (NHIS) shows that the incidence rate of CTS in the general population is 2.6 million. Bank employees are one of the professions prone to CTS due to their computer typing activities. This study aims to determine the relationship between the duration of work and body position during typing and the occurrence of CTS among computer users at BNI in Denpasar City. Methods: This study used a cross-sectional study design and purposive sampling technique for subject recruitment. The total sample size in this study was 86 BNI employees who use computers in Denpasar City. Data collection was conducted through interviews to determine the duration of work and specific examinations such as Phalen’s and Tinel’s tests, and researchers measured the body position of employees during typing using the Rapid Upper Limb Assessment (RULA). Results: The chi-square test analysis yielded a p-value of 0.039, indicating a relationship between the duration of work and the occurrence of CTS, and a p-value of 0.002, indicating a relationship between body position during typing and CTS. Conclusion: The study concludes that there is a relationship between the duration of work and body position during typing and the occurrence of CTS among computer users at BNI in Denpasar City. Providing ergonomic training and education by the institution, managing work time and modifying workstations, followed by light stretching by the subjects, can reduce the risk and severity of CTS occurrences. Keywords: carpal tunnel syndrome, duration of work, body position during typing